Environmental Health in Nicaragua : Addressing Key Environmental Challenges - World Bank (Washington, DC, 2014)
The Latin America and Caribbean (LAC) region has a unique mix of qualities and challenges when it comes to the environment. It is exceptionally endowed with natural assets, with globally significant biodiversity and valuable crops, and also harbors the world s greatest carbon sink in the Amazon. The purpose of the series is to contribute to the global knowledge exchange on innovation in environmental and water resources management and the pursuit of greener and more inclusive growth. The series addresses issues relevant to the region s environmental sustainability agenda from water resources management to environmental health, natural resource management, biodiversity conservation, environmental policy, pollution management, environmental institutions and governance, ecosystem services, environmental financing, irrigation and climate change and their linkages to development and growth. In this particular paper, the author presents the findings of a study looking at three fundamental environmental health risks in Nicaragua, notably inadequate water and sanitation, indoor and outdoor air pollution. The results are striking in that these three risks alone amount to an estimated 2.4 percent of the country s gross domestic product (GDP), affecting primarily the poorer segments of the population. The study proceeds to look at priority investments and solutions, including by ranking potential interventions in terms of their costs and the expected benefits.